Immunochromatographic method in the diagnosis of pneumococcal respiratory tract diseases - V. V. Nikolenko; N. N. Vorobyeva; I. V. Feldblum; S. O. Golodnova (Журнал инфектологии)
Streptococcus pneumonia – one of the reasons for the appearance of complications from influenza and acute respiratory diseases, occurring with a lesion of ENT organs and respiratory system. In this regard, there is a substantial need for the use of additional methods of laboratory testing for verification of pathogen. Diagnostics of complications from respiratory diseases caused by pneumococcal flora has been carried out by immunochromatographic assay. Microbiological examination revealed the pneumococcal etiology of complications only in 14,0% of cases, but verification of diagnosis by detection of Streptococcus pneumonia antigen in the urine in 29,8%.